KEPEMIMPINAN PEMERINTAHAN DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA PEKANBARU TAHUN 2013-2016 - Desthy Nur Ainun Isnaini; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Population and Civil Registration Department in Pekanbaru City reach Predicate Compliance Standards in the Public Service Act No. 25 of 2009 on Public Service in 2014 given by OMBUDSMAN Republic of Indonesia. Additionally, Populatin and Civil Registration Departmen in Pekanbaru City has been named as a reference model in order to 11 from 57 regencies/cities in Indonesia and used as role modeling One Stop Services (OSS) awarded by the Ministry of Administrative Reform and Bureaucratic Reform (PANRB). This makes some regions perform comparative studies to follow the innovation and the services provided to the civil society by Population and Civil Registration Department in Pekanbaru city. The method used in this research is descriptive method with qualitative research. Type of research data is primary data and secondary data. Data collection techniques in this study is documentation, observation and interviews. Technical analysis of the data used is descriptive qualitative data analysis.The results of this research is Population and Civil Registration Department in Pekanbaru City has a program, namely: Improving the quality of human resources through improvement of excellent service to the community, Doing cooperation with the Agency, Provides Services with Ball Pick Systems, and Guidance or Socialization of Population Administration For Civil Society. Factors that affect the successful of Population and Civil Registration Department in Pekanbaru City are: the information requirements, the completion period information, the charges information, facilities, infrastructure, and/or facilities, executive competence, their handling of complaints, suggestions, and feedback.Keywords: Leadership Administration, Population and Civil Registration Department in Pekanbaru